放線菌感染症を治療するための組成物及び方法 (2025)
本開示は、例えば、マイコバクテリア細胞により引き起こされる放線菌（例えば、コリネバクテリウム目）感染症の治療のための組成物及び方法に関する。一態様では、本開示は、（ａ）溶解素Ａ；（ｂ）溶解素Ｂ；（ｃ）イソアミラーゼ；及び（ｄ）α－アミラーゼのうちの１つ以上を含む未封入タンパク質を含有する組成物に関する。組成物は、（ａ）溶解素Ａ；（ｂ）溶解素Ｂ；（ｃ）イソアミラーゼ；及び（ｄ）α－アミラーゼのうちの１つ以上を含む超分子構造体をさらに含んでもよい。別の態様では、本発明は、対象における細菌感染症の治療方法であって、本明細書に記載する未封入溶解タンパク質の組成物を上記対象に、任意選択的に、封入溶解タンパク質と組み合わせて、細菌感染症を治療するのに十分な量及び時間投与することによる、上記方法に関する。封入溶解タンパク質及び未封入溶解タンパク質は、同一または異なった組成物であることができ、同時にまたは連続的に投与することができる。 The present disclosure features compositions and methods for the treatment of actinomycetia (e.g., corynebacteriales) infections, e.g., caused by mycobacterial cells. In one aspect, the disclosure features a composition containing unencapsulated proteins that include one or more of (a) a Lysin A; (b) a Lysin B; (c) an isoamylase; and (d) an α-amylase. The composition optionally further includes a supramolecular structure including one or more (a) a Lysin A; (b) a Lysin B; (c) an isoamylase; and (d) an α-amylase. In another aspect, the invention features a method of treating a bacterial infection in a subject by administering a composition of unencapsulated lytic proteins as described herein to the subject in an amount and for a duration sufficient to treat the bacterial infection, optionally in combination with encapsulated lytic proteins. The encapsulated lytic proteins and the unencapsulated lytic proteins can be in the same or different composition and can be administered simultaneously or sequentially.